Problems and Challenges for Digital Literacy-Based Learning Literature Review in the Success of Online Learning in Higher Education - suheri, suheri (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2020)
The presence of technology and industry 4.0 which is identical to the digital and virtual world has changed the paradigm and mindset of life. This mindsdkkso penetrated the world of learning specifically millennial generation. Likewise, learning strategies, models, methods and techniques also began to improve. From the teacher center to the student center, from Behavioristic to Constructivistic, even from text books to virtual books, including from off line learning (traditional) online learning is now present. Online learning Many empirical studies have been carried out to examine problems in virtual and digital-based learning, online learning, online courses, and even online (distance) lectures that emphasize aspects of digital literacy. However, only a few have synthesized the studio beforehand and provided opinions on online shopping competitions and literacy traditions. This review of the literature review was carried out using a Cooper framework aimed at discussing these problems. The three main agreed categories of findings are first, related to online learners 'challenges, secondly to instructors' challenges, and content literacy development editions. The challenges of spending expectations, readiness, identity, and participation of students in online learning. The challenges of the instructor above, above, from the central teacher to the student center, from face to face online, the transition from textbooks to virtual books, time management, and teaching styles. The problem of developing literacy content that discusses the role of content development, multimedia integration, the role of learning strategies in developing literacy content, and plagiarism considerations. To overcome challenges in technology education and literacy, educational institutions need to provide professional development for instructors, training for students, and technical support for content development